Violation of judicial oath as the constitutional as the responsibility of judges - Овчаренко, О. М. (Problems of legality, 2013)
The author analyzes breaches of judicial oath as a reason for legal liability of a judge. Based on the provisions of national legislation, judicial practice, and international legal standards significant signs of the violation of judicial oath are presented.